Multi‐criteria decision making support tool for freight integrators: Selecting the most sustainable alternative - Simongáti, Győző (Transport, 2010)
Sustainable development has turned into a daily concept by now. Similarly, sustainable transport also appears increasingly often, primarily in transport policy and strategic plans. However, it would be equally important if we could apply this aspect for certain activities such as haulage and forwarding that are a part of transport. Today, forwarders select an optimal alternative concerning only the criteria related to the economic effectiveness of the transport task. In many cases, shippers are not aware neither of the concept of sustainable transport nor of harmful effects they generate. Hence, although there is a concept of ‘freight integrator’, only very few are able to meet the requirements laid down for it. No widespread method has been developed yet to compare transportation options. A similar situation can be faced discussing a traditional, purely economic approach and a theoretical modern aspect that would be in accordance with the principles of sustainable transport. The model that was developed at the Department of Aircraft and Ships of Budapest University of Technology and Economics was designed specifically to compare various options in terms of sustainability. The indicators as the elements of decision-making criteria applied in the model were derived from the indicators used for assessing the transport sector but modified according to the requirements of the decisionmaking task for a freight integrator. Finally, such sustainable performance index of certain alternatives is determined by two fundamentally different aggregation methods as ‘fineness index’. This article presents the model structure and application using a concrete example. First published online: 24 Jun 2011